Estudio de los efectos de tolueno, xileno o benceno sobre al reactividad a adrenalina en la preparación de corazón aislado de rata - Alvarado Gómez, Nallely (Universidad Michoacana de San Nicolás de Hidalgo, 2013)
Inhalants are volatile substances at room temperature that are inhaled with the purpose of altering the state of consciousness and rarely are abused by routes other than inhalation. In our country, inhalants are the second most-used drug between street children and teenagers and in our state inhalants are the main drugs used between high school students. Inhalants are classified in four categories: volatile solvents, aerosols, gases and nitrites. People can come in contact with solvents through occasional exposure, occupational exposure and exposure during abuse episodes. The biggest risk associated with inhalant abuse is a process known as sudden sniffing death, which occurs after being exposed to solvents and be subjected to any stressful situation, such as being caught by the police, parents, etc.; epidemiologic reports indicate that the inhaler runs few feet and drops dead suddenly, but the mechanisms by which these effects are produced are still unknown. However, early studies report that cardiac arrhythmias due to 'sensitization' of the heart to epinephrine is probably the most common cause of death; based on this evidence, in the present work we tested the hypothesis that exposure to abused solvents produces an increase in the reactivity of the heart to the effect of epinephrine, which is associated with alterations in the expression of cardiac adrenergic receptors.

Los inhalables son sustancias volátiles a temperatura ambiente, que se inhalan con el propósito de alterar el estado de conciencia y rara vez son administrados por otra vía que no sea la de la inhalación. En nuestro país se encuentran en segundo lugar de consumo en niños y jóvenes de 12 a 18 años, y en nuestro estado se encuentran en primer lugar de consumo entre estudiantes de preparatoria. Los inhalables se clasifican en cuatro grupos: disolventes volátiles, aerosoles, gases y nitritos. Se puede entrar en contacto con los disolventes de abuso por exposición ocasional, ocupacional y de abuso. El mayor riesgo asociado al abuso de los inhalables es un proceso conocido como muerte súbita por inhalación, el cual ocurre después de haber estado expuesto a los disolventes y ser sometido a alguna situación de estrés, como ser sorprendido por la policía, los padres, etc.; los reportes epidemiológicos indican que el inhalador corre unos cuantos metros y cae muerto repentinamente, pero los mecanismos por los cuales se produce no se conocen con exactitud. Sin embargo, estudios anteriores reportan que las arritmias cardiacas, debido a una "sensibilización" del corazón a la adrenalina son probablemente la causa más común de muerte.
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias de la Salud
Keywords: info:eu-repo/classification/cti/3; FCMB-M-2013-1254; Inhalables; Volátiles; Arritmias; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2953